1990
DOI: 10.7870/cjcmh-1990-0022
|View full text |Cite
|
Sign up to set email alerts
|

Leisure, Health, and Disability: A Review and Discussion

Abstract: There is growing evidence that leisure is an important aspect of people's lives. The satisfactions gained from leisure often outweigh those gained from employment or other work activities. Individuals with disabilities are no exception to this phenomenon. Opportunity to engage in leisure activities of one's choosing is paramount to a disabled person's health and well-being. The purposes of this article are to: (a) describe the potential benefits of participation in recreation and leisure to individuals with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 0 publications
2
15
0
2
Order By: Relevance
“…These results show some similarity with other research reported in the literature (Shields et al, 2006). These data are consistent with most research in the area, where the positive effect of participation in free time activities and recreation is mentioned as improving personal and social skills, health and wellbeing (Caldwell & Gilbert, 1990;King et al, 2003;Simeonsson et al, 2001). …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These results show some similarity with other research reported in the literature (Shields et al, 2006). These data are consistent with most research in the area, where the positive effect of participation in free time activities and recreation is mentioned as improving personal and social skills, health and wellbeing (Caldwell & Gilbert, 1990;King et al, 2003;Simeonsson et al, 2001). …”
Section: Resultssupporting
confidence: 91%
“…With regard to participation in recreational and free time activities, the results are in line with other studies (Caldwell & Gilbert, 1990;King et al, 2003), which accentuate the powerful effect of this variable in the development of personal and relational skills, and in particular in self-concept. Efforts should therefore be made in this area with the design of formal and informal programmes and socioeducational activities, both individually and in groups, to encourage the participation of adolescents in these enriching activities.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Among youth 6 to 12 years, bladder needs were not related to participation; however, bowel issues limited their involvement in physical and social activities (Table 6). Discussion Participation is key to child development, contributing to life satisfaction but also preparing one for future roles [8,17,24]. However, youth with disabilities participate in fewer activities and less often than children without disabilities [13].…”
Section: Resultsmentioning
confidence: 99%
“…Participation has been discussed as key to life success and happiness [18,27]. For youth, participation has the potential to contribute to life satisfaction and preparation for critical adult roles [8,17,24]. Despite this, research indicates low levels of participation among youth with disabilities.…”
Section: Introductionmentioning
confidence: 99%